Are Newspapers' Online Discussion Boards Democratic Tools or Conspiracy Theories' Engines? A Case Study on an Eastern European "Media War". (December 2016) - Slavtcheva-Petkova, Vera
This article analyzes quantitatively and qualitatively 1, 583 comments by national newspapers' online readers in Bulgaria. It investigates readers' reactions to articles discussing the media war between the biggest press groups—one owned by a Member of Parliament known as "the Murdoch of the East." The study explores how these stories influence the relationship between newspapers and their readers, and whether they enhance the democratic potential of online discussion. The results show a higher level of reader engagement than in established democracies or nondemocracies. The online space provides an arena for democratic conversations and it is also used as an engine for conspiracy theories.